PERTIMBANGAN HAKIM DALAM PENJATUHAN PUTUSAN TERHADAP PELAKU TINDAK PIDANA PEMBAJAKAN DI PANTAI LAUT - Galang Fadillah Rahmawan (LPPM Universitas Bina Bangsa, 2022)
The purpose of this study is to find out the accountability of the perpetrators of criminal piracy on the sea coast and the basis of the judge's consideration in the enforcement of the verdict against the perpetrators of piracy on the sea coast. The research approach used in this research is through normative juridical approach and empirical approach using secondary data and primary data, then qualitative juridical data analysis is carried out. The results of the study that the accountability of perpetrators of piracy on the sea coast was found guilty of violating Article 439 paragraph (1) jo Article 55 paragraph (1) to 1 of the Criminal Code and sentenced to prison for 2 (two) years and 7 (seven) months and the basis of the judge's consideration in the conviction of the perpetrator of piracy on the sea coast, namely evidence, witness testimony, Expert information, indictments and demands of the Public Prosecutor, elements that meet in the Prosecutor's Indictment, as well as incriminating and mitigating matters in the accused. All aspects considered by the Panel of Judges are legal facts revealed in the trial, both juridical and nonjuridical aspects